Predictors of ambulance use in patients with acute myocardial infarction in Australia. Issue 12 (27th November 2006) - Kerr, D; Holden, D; Smith, J; Kelly, A-M; Bunker, S
Abstract : Aims: To determine ambulance transport rates and investigate predictors for ambulance use by patients with acute myocardial infarction (AMI) in Australia. Methods: A prospective, cross-sectional descriptive survey using structured interviews. It included patients who were admitted to two hospitals (Western, Bendigo, Melbourne, Victoria, Australia) with AMI between 1 October 2004 and 31 March 2005, and data were collected by semistructured interview and medical record review. Data were analysed by descriptive statistics, univariate and multivariate analysis using SPSS. Results: 105 patients were interviewed. 48 (46%) participants called for an ambulance as their initial medical contact. Participants who called for an ambulance had a shorter interval between symptom onset and presentation to hospital than those who did not (non-ambulance participants)(median 2.1 v 7.8 h; p = 0.001). Predictors of ambulance transport were older age (p = 0.008), symptom onset on the weekend (p = 0.022), presence of sharp chest pain (p = 0.011), self-administered anginine (p = 0.007), symptom onset at home (p = 0.027) and having a lower income (<A20 000; p = 0.022). After multivariate analysis, self-administered anginine, sharp chest pain and occurrence of symptom onset at home remained as independent predictors of ambulance use. Conclusion: A substantial number of patients do not call for an ambulance as their first medical contact after the onset of AMI symptoms. Public education on the benefits of ambulance transport and early treatment, as well as recognition of AMI symptoms, is required.